Scientific investigation of metakaolin-based cement concrete with rock sand infill. (2022) - Sharma, Prashant; Sharma, Neha; Kumar Parashar, Arun
Abstract: Concrete containing pores may perform poorly, when exposed to high shrinkage and settlement rates. The purpose of this study was to use Metakaolin and rock sand to improve concrete performance by reducing voids. Metakaolin has proven to be an effective supplemental cementitious ingredient in cement concrete. The most commonly utilised additives in concrete are metakaolin and its characteristics. Because metakaolin is widely available in our country, it may bring economic benefits when used in cement concrete. A substitution proportion of metakaolin of 5 percent, 10 percent, 15 percent, 20 percent, and 25 percent by weight of cement was to be used. Concrete is tested by casting cubes and cylinders to see how long it lasts and how strong it is. In 15 percent MK-based concrete, increases in compressive strength of 47.55 percent, 27.88 percent, and 47.52 percent were found after 7, 28, and 90 days, respectively.